Development Strategy in Bio-Geophysic Ecological Area of Mandeh Tourism to Meet Asean Economic Community (MEA) - Syam, Alexander (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
The purpose of this study is to determine and analyze Mandeh tourism development strategy and to formulate Development Alternatives using FGD (Focus Group Discussion) and AHP (Analytical Hierarchy Process). The type of this study is Mixed Method which is research that combines or integrates qualitative and quantitative Method to be used together in research activities in order to obtain more comprehensive, valid, reliable, and objective data. However, in this study is more weighted on qualitative research and quantitative data to support qualitative research. So, based on the results of FGD and AHP there are four main priorities strategy in dealing MEA: 1) tourism development of art, culture and religion, 2) tourism product’s development of natural wonder, 3) development of underwater tourism, 4) providing socialization to meet MEA.